ANALISIS EFEKTIVITAS STRATEGI PEMASARAN JASA TELEKOMUNIKASI (STUDI EVALUASI PERSEPSI KONSUMEN PADA SEGMENTASI YOUTH PT TELKOMSEL WILAYAH PEKANBARU) - Colliny, Artharia; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of research is to determine and analyze consumer perseptions oftelecommunications sevices marketing strategy on PT Telkomsel RegionPekanbaru. Youth segmentation is targeting market focus of young people’s whoapplied by PT Telkomsel in maintaining position as market leader. Thissegmentation succes by implementing a marketing strategy that measures theeffectiveness of the strategy through consumer perceptions.Consumer perceptionsconsists of 7 dimensions (7)perception of the product, perception of the price,perception of the location, perception of the promotion, perception of the fieldteam, perception of the innovative and up to date youth life style, perception of theknowledge and experience consumers.in research the population is youthconsumer segmentation at PT Telkomsel Region Pekanbaru. Sampling techniqueis accidental sampling and using slovin formula so obtained were 100respondents. The results that effectiveness of the marketing strategies oftelecomunication services, consumer perceptions on youth segmentation at PTTelkomsel Region Pekanbaru in neutral category.Keyword: effectiveness of marketing strategy,telecommunications, youthsegmentation.